Analysis of Microglia Morphology and Number in Wistar Rats Brain After CIDR1α-PfEMP1 Recombinant Protein Injection - Sulistyaningsih, Erma; Putri, Izza Amalia; Rachmania, Sheilla (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractOne malaria vaccine candidate is Cysteine-rich Interdomain Region 1α (CIDR1α) of Plasmodium falciparumErythrocyte Membrane Protein 1 (PfEMP1), an essential protein involved in the pathogenesis of cerebral malaria. Microglia in the brain act as the first line of defense against brain pathological changes. The study aimed to evaluate the response of brain microglia to the CIDR1α-PfEMP1 recombinant protein injection by observing microglia morphology and number in rat’s cerebral cortex. 12 Wistar rats were divided into the control group, which was injected with normal saline solution, and the treatment group, which was injected with 150 µg CIDR1α-PfEMP1 recombinant protein combined with adjuvants. Injection was conducted thrice within three-week intervals (day 1, 21, and 42). Wistar rats were euthanized on day 56, and histological slides were prepared with Hematoxylin-Eosin staining. Examination using a microscope, 400x, and Fiji Image J software showed microglia morphology of ramified and rod cells in both the control and treatment groups. The microglia number in the control group was 93.00 ± 5.77, and the treatment group was 105.75 ± 15.62. Statistical analysis using an independent t-test showed no significant differences between groups (p= 0.15). The result indicated that the injection of CIDR1α-PfEMP1 recombinant protein did not provoke pathological changes in brain tissue, which induced a microglia response. This study strengthens the potential of the CIDR1α-PfEMP1 recombinant protein as a peptide-based malaria vaccine candidate.AbstrakSalah satu kandidat vaksin malaria adalah Cysteine-rich Interdomain Region 1α (CIDR1α) dari Plasmodium falciparum Erythrocyte Membrane Protein 1 (PfEMP1), protein penting dalam patogenesis malaria serebral. Mikroglia di otak berperan sebagai pertahanan lini pertama terhadap perubahan di otak. Penelitian ini bertujuan mengevaluasi respon mikroglia otak terhadap pemberian protein rekombinan CIDR1α-PfEMP1 dengan mengamati morfologi dan jumlah mikrolia pada korteks serebri otak tikus. 12 tikus Wistar dibagi dalam kelompok kontrol yang diinjeksi normal saline dan  kelompok perlakuan diinjeksi 150 µg protein rekombinan CIDR1α-PfEMP1 yang dikombinasikan dengan adjuvant. Injeksi dilakukan tiga kali dengan interval tiga minggu (hari 1, 21, dan 42). Tikus dieuthanasia pada hari ke-56 dan preparat histologi otak disiapkan dengan pengecatan Hematoxyline-Eosin. Pengamatan menggunakan mikroskop 400x dan Fiji Image J software menunjukkan morfologi ramified dan rod cell pada kelompok kontrol maupun perlakuan. Jumlah mikroglia pada kelompok kontrol 93,00 ± 5,7 sedangkan kelompok perlakuan 105,75 ± 15,62). Analisis statistik menggunakan independent-t test menunjukkan tidak terdapat perbedaan yang bermakna antara 2 kelompok (p= 0,15). Hasil ini mengindikasikan bahwa pemberian protein rekombinan CIDR1α-PfEMP1 tidak menimbulkan patologi pada jaringan otak yang memicu respon mikroglia. Hal ini menguatkan potensi protein rekombinan CIDR1α-PfEMP1 sebagai kandidat vaksin malaria berbasis peptida.